2017
DOI: 10.5194/acp-17-3301-2017
|View full text |Cite
|
Sign up to set email alerts
|

A possible pathway for rapid growth of sulfate during haze days in China

Abstract: Abstract. Rapid industrialization and urbanization have caused frequent occurrence of haze in China during wintertime in recent years. The sulfate aerosol is one of the most important components of fine particles (PM 2.5 ) in the atmosphere, contributing significantly to the haze formation. However, the heterogeneous formation mechanism of sulfate remains poorly characterized. The relationships of the observed sulfate with PM 2.5 , iron, and relative humidity in Xi'an, China have been employed to evaluate the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
110
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 198 publications
(125 citation statements)
references
References 47 publications
7
110
1
Order By: Relevance
“…34 reported that α-Fe 2 O 3 achieved the best performance in the catalytic oxidation of SO 2 among different crystal phases of iron oxides. In particular, a recent inclusion of parameterization into models simulation involving Fe 3+ -catalyzed SO 2 heterogeneous oxidation in aerosol water successfully reproduced the rapid sulfate growth during haze days in China 11 . Both iron and relative humidity played key roles in promoting the uptake of SO 2 to aerosol surface, with a high reactive uptake coefficient of 0.5 × 10 −4 assuming enough alkalinity in the catalytic reaction 11 .…”
Section: Introductionmentioning
confidence: 94%
“…34 reported that α-Fe 2 O 3 achieved the best performance in the catalytic oxidation of SO 2 among different crystal phases of iron oxides. In particular, a recent inclusion of parameterization into models simulation involving Fe 3+ -catalyzed SO 2 heterogeneous oxidation in aerosol water successfully reproduced the rapid sulfate growth during haze days in China 11 . Both iron and relative humidity played key roles in promoting the uptake of SO 2 to aerosol surface, with a high reactive uptake coefficient of 0.5 × 10 −4 assuming enough alkalinity in the catalytic reaction 11 .…”
Section: Introductionmentioning
confidence: 94%
“…In addition, the underestimation of emissions from upwind regions or strong wet scavenging of aerosols during transport could be another reason for the simulated low bias (Yang et al, 2017). Too low a rate of transformation from SO 2 gas to sulfate particles in the model could also contribute to the low bias in sulfate concentrations (Wang et al, 2016;Li et al, 2017). The bias can also result from the fact that the site measurements are point observations, while the model results are grid-cell average that does not consider subgrid aerosol variations (Qian et al, 2010;.…”
Section: Model Evaluationmentioning
confidence: 99%
“…A recent study by Wang et al (2016) focusing on the sulfate pollution over China and London found that aqueous oxidation of SO 2 by NO 2 was key to efficient sulfate formation, which has typically been neglected in atmospheric models and is not considered in the CAM5. Another study by Li et al (2017) found that including an aerosol water (HRSO 2 ) parameterization in SO 2 oxidation in a box model could reproduce the observed rapid sulfate formation in Xi'an over China. More rapid oxidation of SO 2 would reduce SO 2 loss by dry and wet removal and increase sulfate production, which can partly explain the low bias in the simulated sulfate concentrations and high bias in SO 2 .…”
Section: Model Evaluationmentioning
confidence: 99%
“…Over the past 3 decades, rapid industrialization and urbanization have caused severe air pollution in China, particularly during wintertime heavy haze, with extremely high levels of fine particles (PM 2.5 ) frequently engulfing the north of China (e.g., Chan and Yao, 2008;Fang et al, 2009;Zhao et al, 2013;Huang et al, 2014;Guo et al, 2014;Li et al, 2017a). Elevated atmospheric aerosols or PM 2.5 not only influence the Earth's climate system, but also remarkably impair visibility and potentially cause severe health defects (e.g., Penner et al, 2001;Pope and Dockery, 2006;.…”
Section: Introductionmentioning
confidence: 99%